2016
DOI: 10.1021/acs.analchem.6b01788
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Induced FRET via Polymer–Surfactant Complexation: A New Strategy for the Detection of Spermine

Abstract: A new water-soluble cationic conjugated polymer [9,9-bis(6'-methyl imidazolium bromide)hexyl)fluorene-co-4,7-(2,1,3-benzothiadiazole)] (PFBT-MI) was designed and synthesized via Suzuki cross-coupling polymerization in good yields without any tedious purification steps. PFBT-MI showed excellent photophysical responses toward SDS and SDBS with a detection limit of 0.12 μM/(34 ppb) and 0.13 μM/(45 ppb), respectively. Furthermore, occurrence of FRET from the donor (fluorene) to acceptor (BT units), via surfactant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 62 publications
0
56
0
Order By: Relevance
“…Working ranges are mainly up to two decades. Wider ranges than 2 decades have the systems based on PFBT-MI and surfactant [ 6 ] and Tyrosine-protected gold nanoparticles [ 29 ]. CR-528 and CR-555 offer wider working range for the detection of NaSH than the fluorescent probe HF-PBA [ 26 ] and 4-chloro-7-nitrobenzofurazan [ 25 ] do for H 2 S. Apart from Tyrosine-protected gold nanoparticles [ 29 ], the chromoreactands provide the lowest working range for the detection of spermine and spermidine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Working ranges are mainly up to two decades. Wider ranges than 2 decades have the systems based on PFBT-MI and surfactant [ 6 ] and Tyrosine-protected gold nanoparticles [ 29 ]. CR-528 and CR-555 offer wider working range for the detection of NaSH than the fluorescent probe HF-PBA [ 26 ] and 4-chloro-7-nitrobenzofurazan [ 25 ] do for H 2 S. Apart from Tyrosine-protected gold nanoparticles [ 29 ], the chromoreactands provide the lowest working range for the detection of spermine and spermidine.…”
Section: Resultsmentioning
confidence: 99%
“…Biogenic amines are nitrogen-containing low molecular weight organic compounds that are naturally synthesized in animals, plants, and microorganisms—generally by decarboxylation of free amino acids or by amination or transamination of aldehydes and ketones [ 5 ]. Certain biogenic amines, like spermine and spermidine, are among the most abundant organic polycations that are found in the human body, involved in protein synthesis, conformational stabilization of nucleic acids, and cytoskeleton structures, and they play multiple roles in cell growth, proliferation, and survival [ 6 , 7 ]. Consequently, changes in levels of spermine and spermidine have been associated with aging and diseases, like cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the optimal conditions in a blank matrix, by taking the logarithm of the absorbance ratio, a linear SPM calibration curve from 0–5 μ m could be fitted by least‐squares linear regression (Figure ). The equation was y= 0.1029×−0.4941, with the limit of detection (LOD) calculated to be 15.25 n m (3.09 ng mL −1 ) by the equation LOD=3 σ of absorbance in the absence of SPM/slope of curve . TEM images clearly showed the increase of AuNP aggregation extent in an increasing amount of SPM content (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…Optical sensors have been applied to determine biogenic amines in various food and beverages such as histamine, tyramine, ethylamine, putrescine, agmatine, isopentylamine, methylamine and propylamine by using speci c indicator dyes that exhibit di erent spectral characteristics when exposed to these analytes (Kumpf et al (2015); (Mastnak et al, 2018); Nedeljko et al (2017); Rawat et al (2017)). Malik et al (2016) reported the biogenic amines determination in liquid samples where this study synthesized the water-soluble cationic conjugated polymer using [9,9-bis(6'-methylimidazoliumbromide)hexyl)-uorene-co-4,7-(2,1,3-benzothiadiazole)](PFBT-MI) and combined it with a surfactant in order to acquire aggregates, which enabled the spermine detection. Rawat et al (2017) on the other hand, used tyrosine-protected gold nanoparticles (Tyr-Au-NPs) as a dual probe for colorimetric and uorescene turn-on assays of spermine and spermidine in biological samples.…”
Section: Optical Sensorsmentioning
confidence: 99%